Knowledge and attitude of school students regarding COVID-19 pandemic - Waghmare, Pooja; Humane, Sushil; Shaikh, Tasleem (International Journal Of Community Medicine And Public Health, 2023)
Background: In India, a variety of approaches was adopted to control the spread of COVID-19 among people including social distancing, compulsion on wearing a mask, and vaccination. However, there is still lacking the awareness among people regarding COVID-19. knowledge and attitude of the youth can make a huge difference in these efforts and so this study is aimed to find the knowledge and attitude of school students regarding COVID-19. Methods: A descriptive study was conducted in September 2021 on a total of 286 school students. Different schools in Nagpur were used to collect data from students aged between 15-18 years. Prior consent and accent were taken from the parent and students respectively before data collection. A convenient sampling technique was used to collect data by using the demographic form, structured knowledge questionnaire (SKQ), and attitude Likert scale (ALS). Results: In the study group, 37.06% were in 16-17 years of age, 57.69% were male, 32.87% were in 11th standard, about 55.94% of student’s parents were doing the private job, 39.51% of student’s family income was between 10001-20000, 46.85% students were living in a nuclear family, 89.16 students had previous knowledge of COVID-19 and about 71.37% of student got this knowledge from the television. In the study group, 5.94% of students had Good knowledge and 35.66% of students had a favorable attitude. Conclusions: The majority of the school students have poor knowledge and attitude toward COVID-19. Educational intervention is very necessary to improve the knowledge of students.